Implementation of the Pancasila Learner Profile Strengthening Project: Perceptions of Future Elementary School Educators - Siti Nurwita Sekar Suci; Herwin Herwin; Zeva Adi Fianto; Fitri Indriani (Universitas Pendidikan Ganesha, 2024)
The high incidence of antisocial behavior such as bullying and early exposure to social media that affects students' character highlights the urgency of strengthening character education in schools. The Pancasila Student Profile Strengthening Project (P5) is one of the strategic steps that has begun to be implemented. This study aims to analyze prospective elementary school teachers' perceptions of the implementation of P5. This is a descriptive quantitative research using a survey method. The research subjects in this study were 53 elementary school teacher education students. Data collection was conducted by distributing questionnaires to students using Google Forms. The data obtained were in the form of scales, as the questionnaires were distributed using a 1-5 Likert scale. Data analysis was carried out by converting quantitative data into qualitative data based on a table of prospective elementary school teachers' perceptions. The analysis results indicate that prospective elementary school teachers have a positive perception of the implementation of P5, categorized as “agree.” They assess P5 as beneficial in enhancing social awareness, cooperation, creativity, and respect for diversity. With this positive response, it is hoped that schools will continue to implement P5, as it has proven effective in shaping students' character in accordance with the Pancasila Student Profile.